2016
DOI: 10.1111/epi.13506
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of epilepsy and electroencephalographic abnormalities due to SHANK3 loss‐of‐function mutations

Abstract: Summary Objective The coincidence of autism with epilepsy is 27% in those individuals with intellectual disability1. Individuals with loss of function mutations in SHANK3 have intellectual disability, autism and variably, epilepsy2–5. The spectrum of seizure semiologies and electroencephalographic (EEG) abnormalities has never been investigated in detail. With the recent report that SHANK3 mutations are present in approximately two percent of individuals with moderate to severe intellectual disabilities and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 28 publications
3
70
2
2
Order By: Relevance
“…For example, enhanced EEG gamma oscillatory power has been reported across a number of genetic mouse ASD models, consistent with resting state EEG findings in individuals with neurodevelopmental disorders [31, 60, 61]. Such examples include increased gamma power in both Mecp2 and Pten mutant mouse models [62, 63].…”
Section: Discussionmentioning
confidence: 58%
“…For example, enhanced EEG gamma oscillatory power has been reported across a number of genetic mouse ASD models, consistent with resting state EEG findings in individuals with neurodevelopmental disorders [31, 60, 61]. Such examples include increased gamma power in both Mecp2 and Pten mutant mouse models [62, 63].…”
Section: Discussionmentioning
confidence: 58%
“…Lennox–Gastaut syndrome most often follows other types of pharmacoresistant epilepsies including infantile spasms, late‐onset spasms, or myoclonic astatic epilepsy. SHANK3 loss‐of‐function or deletion – common in Phelan–McDermid syndrome – begins with Lennox–Gastaut syndrome in up to 20% of cases …”
Section: Gene Dysfunction In Age‐dependent Epilepsy Phenotypesmentioning
confidence: 99%
“…SHANK3 loss-of-function or deletioncommon in Phelan-McDermid syndromebegins with Lennox-Gastaut syndrome in up to 20% of cases. 47…”
Section: Lennox-gastaut Syndromementioning
confidence: 99%
“…Gene repair or IGF1 interventions can restore excitatory synaptic transmission. It has been suggested that deletions in the SHANK3 gene could possibly mediate the mechanism of epileptic seizures by causing a decrease in excitatory synaptic function …”
Section: Ipsc Studies On the Molecular Mechanisms Of Gementioning
confidence: 99%
“…It has been suggested that deletions in the SHANK3 gene could possibly mediate the mechanism of epileptic seizures by causing a decrease in excitatory synaptic function. [70][71][72][73] Multiple congenital anomalies-hypotonia-seizures syndrome 2 (MCAHS2), characterized by epilepsy, myoclonus, and mental retardation, 74 can be caused by mutations in another membrane protein gene, the phosphatidylinositol glycan class A gene (PIGA), which encodes a phosphatidylinositol glycan class A protein (PIGA), one of the phospholipid elements of the cell membrane. Yuan et al 75 found that iPSCs from patients with PIGA mutations (c.1234C>T) exhibit lower proliferative capacity than normal heterozygotes, fewer induced GABAergic neurons with low maturation levels, aberrant synapse formation, and abnormal membrane depolarization.…”
Section: Mutations Affecting Neurite Maturationmentioning
confidence: 99%